Effect of dynamic adsorption layer over colliding bubble on rate of solid surface dewetting in cationic surfactant solutions. (1st May 2021) - Wiertel-Pochopien, Agata; Kosior, Dominik; Zawala, Jan
Highlights: Dynamic adsorption layer (DAL) influences three-phase line (TPCL) expansion rate. Lack of DAL means slower rate of TPCL expansion. Presence of DAL increases significantly TPCL expansion rate. For fully formed DAL, TPCL expansion rate can be comparable to pure water. Abstract: Influence of a motion induced dynamic adsorption layer (DAL) at a liquid/air interface on a kinetic of three-phase contact line (TPCL) expansion in solutions of n-cetyltrimethylammonium bromide (CTAB - cationic surfactant) was studied. It was found that, independently of the solid surface hydrophobicity (assessed using determination of the receding contact angle values), the DAL presence influences profoundly the velocity of the TPCL expansion. For the quartz surface, where the contact angle was controlled by a CTAB concentration, the TPCL expansion rate correlateds with the degree of solid surface hydrophobicity. However, for similar values of the contact angle, much higher rate of the TPCL rate expansion was observed for the fully formed DAL at the colliding bubble surface. This effect was the most pronounced for receding contact angle equal to ca. 60–70° (i.e. for higher CTAB bulk concentrations). In the case of the highly hydrophobic poly(tetrafluoroethylene) (PTFE) surface, similar observations were reported, despite the fact that the receding contact angle values were independent of the CTAB bulk concentration. For the PTFE surface, additionally, similar TPCL expansion velocities were reported for pure water and CTAB solutions where the DAL structure was fully formed at the colliding bubble interface, suggesting similar liquid/gas interface's hydrodynamic boundary conditions.